La méta-analyse, espace transitionnel de trans-formation en formation de formateurs - Nicole Clerc; Martine Agogué (Université de Provence, 2015)
This article, set within the framework of clinical psychosociology, addresses experts concerned with « human relationship professions ». It aims at defining identity restructuring processes in trainers whose missions have been altered by contemporary society's mutations. The clinical study of a session devoted to a reflexive analysis of practices will enable us to focus on how the moment of « meta-analysis » containing "transitional space", working towards the understanding of psychic processes related to new insights and necessary representational shifts. The type of work described and analysed below rests on a principle of thought association and a logic of contamination. Its aim is the transmission of a shared gesture that will open the way of thinking both suspended and committed. A critical analysis of collected testimonies will allow us to pin down the creative ressources of this transitional space which renews the power to understand and act, and prompts the emergence of a democratic subject within the space delineated by this "thinking together."